2016
DOI: 10.1038/srep26331
|View full text |Cite
|
Sign up to set email alerts
|

PKA-CREB-BDNF signaling regulated long lasting antidepressant activities of Yueju but not ketamine

Abstract: Yueju confers antidepressant effects in a rapid and long-lasting manner, similar to ketamine. CREB (cAMP-response element binding protein) signaling is implicated in depression pathology and antidepressant responses. However, the role of CREB and associated brain derived neurotrophic factor (BDNF) signaling in rapid and long-lasting antidepressant effects remains unclear. Here, we demonstrated that ICR and Kunming strain mice conferred antidepressant responses lasting for 1 and 5 days, respectively, following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 39 publications
1
66
0
Order By: Relevance
“…Our results showed that thioperamide upregulated the BDNF levels, and inhibition of CREB by H89 compromised this effect, suggesting thioperamide promote neural stem cell proliferation through enhancing transcription of BDNF via activating CREB. Our results were consistent with study that activation of PKA/CREB signaling showed ameliorated depressive behaviors through upregulating BDNF expression (Xue et al, 2016), showing that strategies activating CREB/BDNF pathway are beneficial to neurogenesis. Neurotrophins, especially BDNF, are potent modulators of dendritic development.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that thioperamide upregulated the BDNF levels, and inhibition of CREB by H89 compromised this effect, suggesting thioperamide promote neural stem cell proliferation through enhancing transcription of BDNF via activating CREB. Our results were consistent with study that activation of PKA/CREB signaling showed ameliorated depressive behaviors through upregulating BDNF expression (Xue et al, 2016), showing that strategies activating CREB/BDNF pathway are beneficial to neurogenesis. Neurotrophins, especially BDNF, are potent modulators of dendritic development.…”
Section: Discussionsupporting
confidence: 92%
“…CREB is an important regulator for BDNF and GDNF expression [4345]. Chronic antidepressant treatment enhances CREB activation, suggesting CREB as an important mediator for antidepressant treatment [24].…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the control groups received the same volume of vehicle. The dosage of KET was chosen according to our previous research [36]. Thereafter, the animals were subjected to TST and FST.…”
Section: Drugs and Treatmentmentioning
confidence: 99%